Increasing kidney cancer incidence and survival in Estonia: role of age and stage. (2nd January 2019) - Innos, Kaire; Sepp, Teesi; Baburin, Aleksei; Kotsar, Andres; Lang, Katrin; Padrik, Peeter; Aareleid, Tiiu
Abstract: Background: Kidney cancer rates in Estonia are high. The study aimed to examine long-term trends in kidney cancer incidence, mortality and survival in Estonia, with special focus on age, birth cohorts, morphology and TNM stage. Material and methods: Estonian Cancer Registry provided data on all incident cases of kidney cancer (ICD-10 C64), diagnosed in adults (age ≥15 years) in Estonia during 1995 − 2014. Relative survival ratios (RSR) were calculated and excess hazard ratios of dying were estimated with gender, age, period of diagnosis and TNM stage as independent variables. Joinpoint regression modeling was used to calculate estimated annual percentage change for incidence (1970–2014) and mortality (1995–2016) trends. Age-specific incidence rates were presented by birth cohort and period of diagnosis. Results: Incidence increased significantly in both sexes, with the steepest rise seen for localized cancer. Cohort effects were pronounced particularly in men, while period effects were seen from the mid-1980s to mid-1990s in both sexes. Age-standardized five-year RSR for total kidney cancer increased by 13 percentage units (from 53% to 65%) over the study period; the increase was larger for renal cell carcinoma (from 63% to 78%). Survival increases of about five percentage units were seen for stages I/II and III. Age and gender were not associated with excess risk of dying from renal cell carcinoma after adjusting for stage. Conclusion: Estonia is currently among countries with the highest incidence of kidney cancer. The results suggest a combined effect of changing risk profiles in successive birth cohorts and increasing diagnostic activity around 1990. Large survival increase can mostly be attributed to earlier detection, but improved diagnosis and treatment have probably influenced stage-specific survival. High proportion of tumors with unspecified morphology and those with unknown stage among the elderly warrants further investigation of diagnostic and treatment practices.